Use of convalescent plasma in pregnant women with early stage COVID-19 infection in a tertiary care hospital in Dubai, February to March 2021: a case series study - Heba Adan; Deemah Harb; Komal Hazari; Widad Abdelkareem; Fareeda Nikhat Khan; Maryam Zouaoui; May Raouf; Doaa Elsawy; Aida Joseph Azar; Amar Hassan Khamis; Abeer Ammar (BMC, 2022)
Abstract Background The use of COVID-19 convalescent plasma (CCP) for the treatment of SARS-CoV-2 infection in pregnancy is intriguing in view of its safety profile in pregnancy and historical precedence of the use of plasma for other viral illnesses. This study aimed to evaluate the use of CCP in pregnant women with early COVID-19 infection. Methods This is a retrospective case series study. We have included seven pregnant women admitted with early COVID-19 infection to a tertiary care hospital, Latifa Maternity Hospital in Dubai, United Arab Emirates between 12 February and 04 March 2021 and who consented to receive COVID-19 convalescent plasma as part of their treatment plan. Main outcomes measured were clinical and radiological features, laboratory tests, WHO clinical progression scale pre and post treatment, and maternal, fetal outcomes. COVID-19 clinical severity was classified according to the NIH guidelines for criteria of SARS-CoV-2. For the radiological features, a modified chest X-ray scoring system was used where each lung was divided into 6 zones (3 on each side upper, middle, and lower). Opacities were classified into reticular, ground glass, patchy and dense consolidations patterns. Results Seven pregnant women with early COVID-19 were enrolled in this study, their mean age was 28 years (SD 3.6). Four had comorbidities: 2 with diabetes, 1 with asthma, and 1 was obese. Five patients were admitted with a WHO clinical progression score of 4 (hospitalized; with no oxygen therapy) and 2 with a score of 5 (hospitalized; oxygen by mask/nasal prongs). Upon follow up on day 10, 6 patients had a WHO score of 1 or 2 (asymptomatic/mild symptoms) indicating clinical recovery. Adverse reactions were reported in 2 patients, one reported a mild skin rash, and another developed transfusion related circulatory overload. All patients were discharged alive. Conclusion CCP seems to be a promising modality of treating COVID-19 infected pregnant women. However, further studies are needed to ascertain the efficacy of CCP in preventing progressive disease in the management of COVID-19 infection in pregnant women.